Revisiting “Structuring and Supporting UX Work in Academic Libraries” - Shelley Gullikson (Weave: Journal of Library User Experience)
In 2020, Weave published my research article, “Structuring and Supporting UX Work in Academic Libraries” (https://doi.org/10.3998/weave.12535642.0003.202). In it, I examined various ways that academic libraries structure and support user experience (UX) work, and I identified some structures and supports that seemed to have a positive impact on both users and UX workers. Two years after applying those findings to restructure my own position, I did not feel I was having a positive impact. I wondered if I had misunderstood or misrepresented my research participants. I decided to check in with some of them to see where I might have gone wrong.